Spectrophotometric Determination of Lomefloxacin in its Pharmaceutical Dosage Forms - Askal, H.F.; Refaat, I.H.; Darwish, I.A.; Marzouk, M.A. (Asian Journal of Chemistry, 2011)
New highly selective reaction has been proposed as a basis for the spectrophotometric determination of lomefloxacin (LOM), a fluoroquinolone antimicrobial agent. This reaction involved the condensation of lomefloxacin with the oxidized catechol (OXC) and formation of a violet coloured reaction product that exhibited maximum absorption peak at 510 nm. The variables affecting the reaction were carefully investigated and the optimum conditions were established. The stoichiometry of the reaction was determined and the reaction pathway was postulated. The selectivity of the reaction for lomefloxacin among the other fluoroquinolones was evaluated and it was found to be highly selective for lomefloxacin. Under the optimum reaction conditions, Beer’s law was obeyed in the range of 10-60 μg mL-1. The assay limits of detection and quantitation were 2.37 and 7.90 μg mL-1, respectively. The robustness and ruggedness of the method were satisfactory. The method was successfully applied to the analysis of lomefloxacincontaining pharmaceutical dosage forms and the results were statistically compared with those obtained by a pre-validated reference method. No significant differences were found between the two methods in terms of the accuracy and precision as revealed by the accepted values of t- and F-tests, respectively. The proposed method is superior to all the previously reported spectrophotometric methods in terms of its selectivity for lomefloxacin.